MANUSIA SEBAGAI INDIVIDU (Analisis terhadap Kewajiban dan Tanggung Jawab) - Zainuddin Hamkah (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
Every individual is not automatically able to realize his desires, but humans are forbidden to forget God while in the effort to realize these desires in the form of service obligations and responsibilities. For this reason, humans are given the freedom to choose between good and bad things. God himself has given trust to humans so that people always choose the good. God has made